A New Width Measurement Method of the Stress Relief Zone on Roadway Surrounding Rocks. (27th November 2019) - Cui, Pengfei; Yao, Banghua; Liu, Yong; Wei, Jianping; Wen, Zhihui; Li, Hui
Abstract : Determining the width of the stress relief zone on roadway surrounding rocks is the premise to optimize drilling borehole effect and increase gas extraction efficiency. In this study, a new width measurement method of the stress relief zone on the roadway surrounding rocks was proposed, which determined the width according to gas pressure attenuation speeds in roadway boreholes at different depths. Then, the variation curve of the gas pressure in boreholes at different depths with the time was gained through a field test. On this basis, laws of the gas pressure attenuation and the gas transmission and loss in boreholes at different depths were explored through a numerical simulation based on COMSOL Multiphysics, thus concluding the stress on roadway surrounding rocks, the distribution of plastic zones, and the stress-permeability relation. The scientificity of the proposed method was illustrated theoretically. Finally, the proposed method was verified by the field test data and numerical simulation results of the gas extraction at different sealing depths. Research results demonstrate that the pressure in boreholes attenuates in the logarithmic function pattern. The attenuation speed decreases with the increase of the drilling depth. The width of the stress relief zone on roadway surrounding rocks in the studied area was determined to be about 11 m according to the proposed method. Both the numerical simulation and the field test of the gas extraction efficiency prove the feasibility and validity of the proposed method in determining the sealing depth of the borehole for the gas extraction. Research conclusions are of important significance to enrich width measurement methods of the stress relief zone on roadway surrounding rocks and to optimize sealing parameters of underground boreholes for gas extraction.